The effect of self-directed learning in achieving organizational readiness: an exploratory study at the Middle Technical University - Weam Wahhab Alyasiri; Ali Hassoun Al-Tai (Eximia, 2024)
The research aims to determine the extent of the impact of self-directed learning in its dimensions (readiness for self-learning, self-control, desire for self-control, practice) in achieving organizational readiness in its dimensions (cognitive dimension, emotional dimension, behavioral dimension) at Central Technical University. The research started from the main question of By revealing the extent of self-directed learning in achieving organizational readiness, the researchers relied in conducting their research on the descriptive analytical approach on a sample of administrative leaders at the Central Technical University, as they relied on a questionnaire form, in order to collect data by distributing (310) forms, (296) were recovered and tested using a set of statistical programs (EXCEL) and (SPSS 23). The research reached a set of conclusions, the most important of which is the existence of an influence relationship between the dimensions of self-directed learning and the dimensions of organizational readiness, in addition to providing recommendations, the most important of which is holding courses and training programs for learners and gifted people to introduce them to self-directed learning within the university.